2018
DOI: 10.7759/cureus.2176
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Relapse of Chronic Lymphocytic Leukemia After Remission

Abstract: Chronic lymphocytic leukemia (CLL) is the most prevalent leukemia with over 20,000 estimated cases in 2017. Leukemic involvement of the nervous system from CLL causing neurologic symptoms is reported in only about one percent of patients. Unfortunately, there is no current standard therapy for the treatment of CLL leptomeningeal disease. In this case, we discuss an unusual presentation of CLL leptomeningeal disease misdiagnosed as chronic rebound headache.A 61-year-old female was diagnosed with Rai stage I CLL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…10. e2176. 16 61 F Chronic headaches 14 years Rai I NA NA CSF + WW/FCR Ibr 420 mg→560 mg CR Case Rep Hematol. 2018.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10. e2176. 16 61 F Chronic headaches 14 years Rai I NA NA CSF + WW/FCR Ibr 420 mg→560 mg CR Case Rep Hematol. 2018.…”
Section: Discussionmentioning
confidence: 99%
“… 14 It has been reported that an increased dose of Ibr escalates CSF concentration without adverse events, 15 and that increasing the dose of Ibr is effective for CNS lesions in CLL. 16 It will be necessary in the future to verify the optimal dose of Ibr for CNS lesions. Bulky disease in CNS lesion might also cause treatment failure.…”
Section: Discussionmentioning
confidence: 99%